Hubungan Antara Keterlibatan Orang Tua Dan Resiliensi Pada Anak Di Desa Tamansari - Valerama, Agung; Dariyo, Agoes (Universitas Trunojoyo Madura, 2023)
Tamansari Village is part of the Lelea sub-district which is located in Indramayu Regency, West Java. Through brief interviews with several students, indications of behavior that could be classified as bullying behavior were found. Responding to this, the student's parents instilled the values of self-resilience into their son's life.One of the external factors that can help build child resilience is the family. The purpose of this study was to find out whether there is a relationship between parental involvement and resilience in children in Tamansari village. This study used a quantitative approach with 140 elementary school students participating, this research was non-experimental. Participants' ages in this study range between nine to 14 years old. This study also consists of 59 male students and 81 female students. This study also consists of third graders to sixth graders. This study used a purposive sampling technique by distributing questionnaires to elementary school children in grades four, five and six. This study used two measuring instruments, namely the Connor-Davidson Resilience Scale (CD-RISC) adjusted by Campbell-Stein (2007) and also a questionnaire developed by Campbell et al. (1985). The results of the correlation test showed that there was a relationship between parental involvement and resilience in children in Tamansari village (r equal with 0.169, p equal with 0.05, p smaller than 0.046).